2017
DOI: 10.3324/haematol.2016.160432
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological consequences and benefits of HFE mutations: 20 years of research

Abstract: Mutations in the HFE (hemochromatosis) gene cause hereditary hemochromatosis, an iron overload disorder that is hallmarked by excessive accumulation of iron in parenchymal organs. The HFE mutation p.Cys282Tyr is pathologically most relevant and occurs in the Caucasian population with a carrier frequency of up to 1 in 8 in specific European regions. Despite this high prevalence, the mutation causes a clinically relevant phenotype only in a minority of cases. In this review, we summarize historical facts and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 120 publications
(139 reference statements)
1
48
0
5
Order By: Relevance
“…Moreover, both at diagnosis and after a GFD, the celiac patients with H63D mutation, that is, non‐IDA subjects, showed higher hemoglobin and serum iron than those with the wild‐type HFE genotype. Large‐scale population studies have revealed that most HFE mutation carriers with a mild iron overload‐phenotype lack any clinically relevant disease symptoms, leading to the hypothesis that HFE mutations may confer a genetic advantage on asymptomatic hemochromatosis “patients” and have, therefore, continued to spread . The C282Y variant is considered to play the most important role in iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both at diagnosis and after a GFD, the celiac patients with H63D mutation, that is, non‐IDA subjects, showed higher hemoglobin and serum iron than those with the wild‐type HFE genotype. Large‐scale population studies have revealed that most HFE mutation carriers with a mild iron overload‐phenotype lack any clinically relevant disease symptoms, leading to the hypothesis that HFE mutations may confer a genetic advantage on asymptomatic hemochromatosis “patients” and have, therefore, continued to spread . The C282Y variant is considered to play the most important role in iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Während die C282Y-Mutation in Nord-und Mitteleuropa häufig vorkommt, findet sie sich bei südeuropäischen Völkern deutlich seltener und außerhalb Europas nur sehr selten [3]. Aufgrund der geringen Penetranz sowie der geografischen Variabilität werden evolutionäre Vorteile durch die Mutationen diskutiert [4]. Die nicht das HFE-Gen betreffenden Formen II-IV sind deutlich seltener und betreffen im Gegensatz zu Typ I auch nicht europäische Menschen aller Altersgruppen [5].…”
Section: Genetikunclassified
“…Ist dessen Bindungskapazität erschöpft, wird das nicht transferringebundene Eisen vermehrt von Organen wie Leber und Pankreas, aber auch vom Herzen aufgenommen. Die typischen Organdysfunktionen sind Folge der Akkumulation freien intrazellulären Eisens und der Bildung von OH-Radikalen [4].…”
Section: Symptomatikunclassified
“…4) [112][113][114]. Hepatic dysfunction indicated by elevations of serum alanine aminotransferase levels is often observed in the relatively early stages of this disease.…”
Section: Manifestations Of Hhmentioning
confidence: 99%
“…The very high incidences of mutations in the HFE gene among Caucasians evoke the idea that these mutations might have offered advantages to their carriers [114]. For instance, increased iron uptake might have offered advantages to people with a grain-based diet and especially to women of reproductive ages in their survival and reproduction.…”
Section: Evolutional Benefits Of Hfe Mutationsmentioning
confidence: 99%